2015
DOI: 10.1111/pde.12694
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Progressive Mucinous Histiocytosis: New Insights Into a Rare Disease

Abstract: Hereditary progressive mucinous histiocytosis is a rare, benign, skin-limited form of non-Langerhans cell histiocytosis. We report on a 5-year-old boy who presented in infancy with self-resolving dermal nodules but later developed persistent and progressive erythematous papules on the face and scalp. Histologic evaluation revealed dermal aggregates of S-100/CD1a-negative histiocytes with abundant mucin. We present this case to highlight the evolution of the lesional morphology in infancy and early childhood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…HPMH was thought to be a strictly female disease until the publication of 3 cases in men . Case 2 in our series corroborates that HPMH can affect men.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…HPMH was thought to be a strictly female disease until the publication of 3 cases in men . Case 2 in our series corroborates that HPMH can affect men.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, no mucin is observed in the histopathologic study and a hereditary profile has not been observed. Six other families have since been described, all under the designation of HPMH . The clinical, histopathological, and immunohistochemical features of the 15 cases published to date are summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
“…These lesions regress spontaneously. 2,3 It is unclear whether the infantile stage is present in all patients. The second phase starts at a later stage, in childhood and up to early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Papules appear and keep progressing throughout life with no spontaneous resolution. 2 They are smooth, skin-colored or erythematous to red brown, ranging from 1 to 10 mm in size. The lesions are generally asymptomatic, although mild pruritus has been occasionally described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation